Giant resistance switching effect in nano-scale twinned La0.65Ca0.35MnO3 film - Prokhorov, V. G.; Kaminsky, G. G.; Komashko, V. A.; Lee, Y. P.; Tovstolytkin, A. I.; Pogorily, A. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The magnetic and transport properties of a 20 nm-scale twinned La0.65Ca0.35 MnO3 film are investigated in a temperature range of 77-300 K. The coexistence of ferromagnetic metallic and charge-ordered insulating phases is suggested by analyzing the temperature and current dependences of the resistance at low temperatures. It is shown that thermocycling leads to the formation of a nonequilibrium state in the ensemble of charge-ordered domains and to the appearance of a giant switching in resistance of up to 100%. The experimental results are discussed on the basis of phase separation.